Perceptions of patients undergoing palliative care about the occupational impacts experienced in cancer (Revista Contexto & Saúde, 2026)
Objective: The aim of this study is to describe the main occupational repercussions experienced by people undergoing oncological palliative care and to reflect on the impacts. Method: This is a descriptive, cross-sectional study with a qualitative approach, in which the participants were 6 patients over 18 years of age, diagnosed with cancer and receiving palliative care from a home care service. Data collection used a characterization form and an interview guide, with individual interviews conducted during a single meeting in the patient's home. The data from the interviews were categorized, described, and interpreted based on the fourth edition of the Occupational Therapy Practice Framework: Domain and Process document. Results: The average age of the participants was 56.5 years, with the time since receiving the cancer diagnosis varying between 9 months and 13 years. In most cases, participants had been undergoing palliative care for less than 6 months. Two analytical categories were systematized: 1) Occupational repercussions experienced as a result of cancer, in which both interruptions and changes in performance patterns were observed; 2) Impacts of occupational repercussions: understanding the representations intertwined in the experience of losses, in which implications of occupational modifications associated with aspects of satisfaction, beliefs, and adaptive difficulties linked to the disruption of occupational roles were verified. Conclusion: Considering the repercussions and losses experienced as an aspect of potential additional suffering, it is deemed necessary to incorporate the occupational dimension into care planning, in addition to encouraging further research in this area.
Keywords: palliative care; cancer; daily activities; occupational therapy